ART restorations and sealants placed in Chinese school children – results after three years - Holmgren CJ, Lo ECM, Hu DY, Wan HC (Blackwell Synergy, 2000)
These were to assess whether ART restorations and sealants could be provided to children in a school environment in China, to assess patient acceptability of the ART approach, and to evaluate on a longitudinal basis the treatments performed. Methods: This study was conducted in Deyang, Sichuan Province, in western China. A total of 294 ART restorations were placed in 197 children and 191 fissure sealants were placed in 140 children by five middle-level dentists in four secondary schools.